Transitions and animations in CSS : adding motion with CSS - Weyl, Estelle (O'Reilly Media, Inc., 2016)
Add life and depth to your web applications and improve user experience through the discrete use of CSS transitions and animations. With this concise guide, you'll learn how to make page elements move or change in appearance, whether you want to realistically bounce a ball, gradually expand a drop-down menu, or simply bring attention to an element when users hover over it.Short and deep, this book is an excerpt from the upcoming fourth edition of CSS: The Definitive Guide. When you purchase either the print or the ebook edition of Transitions and Animations in CSS, you'll receive a discount on the entire Definitive Guide once it's released. Why wait? Learn how to make your web pages come alive today.Understand and learn how to implement Disney's 12 principles of cartoon animationLearn which CSS properties you can animate and use in transitionsApply CSS's four transition properties and nine animation properties to your CSS...